The insulinogenic effect of whey protein is partially mediated by a direct effect of amino acids and GIP on β-cells - Salehi, Albert (BioMed Central, 2012)
BACKGROUND: Whey protein increases postprandial serum insulin levels. This has been associated with increased serum levels of leucine, isoleucine, valine, lysine, threonine and the incretin hormone glucose-dependent insulinotropic polypeptide (GIP). We have examined the effects of these putative mediators of whey’s action on insulin secretion from isolated mouse Langerhans islets. METHODS: Mouse pancreatic islets were incubated with serum drawn from healthy individuals after ingestion of carbohydrate equivalent meals of whey protein (whey serum), or white wheat bread (control serum). In addition the effect of individual amino acid combinations on insulin secretion was also tested. Furthermore, the stimulatory effects of whey serum on insulin secretion was tested in vitro in the absence and presence of a GIP receptor antagonist ((Pro(3))GIP[mPEG]). RESULTS: Postprandial amino acids, glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide 1 (GLP-1) responses were higher after whey compared to white wheat bread. A stimulatory effect on insulin release from isolated islets was observed with serum after whey obtained at 15 min (+87%, P < 0.05) and 30 min (+139%, P < 0.05) postprandially, compared with control serum. The combination of isoleucine, leucine, valine, lysine and threonine exerted strong stimulatory effect on insulin secretion (+270%, P < 0.05), which was further augmented by GIP (+558% compared to that produced by glucose, P < 0.05). The stimulatory action of whey on insulin secretion was reduced by the GIP-receptor antagonist (Pro(3))GIP[mPEG]) at both 15 and 30 min (−56% and −59%, P < 0.05). CONCLUSIONS: Compared with white wheat bread meal, whey causes an increase of postprandial insulin, plasma amino acids, GIP and GLP-1 responses. The in vitro data suggest that whey protein exerts its insulinogenic effect by preferential elevation of the plasma concentrations of certain amino acids, GIP and GLP-1.